Analisis Hegemoni Negara Dalam Gotong Royong Masyarakat Untuk Pembangunan Desa - Welin, Elisabeth Date Masan; Molan, Kristianus Simon H.; Ethelbert, Yohanes K. (Publikasi Penelitian Terapan dan Kebijakan, 2025)
This research aims to analyze state intervention through village government within the framework of Antonio Gramsci’s hegemony theory, focusing on the dynamics of communal solidarity (gotong royong) in Kenotan Village, Adonara Tengah District, East Flores. The study investigates how state hegemony is exercised in village development, whether traditional practices of gemohing persist or change, and the extent of community participation in the development process. A qualitative method with a case study approach was applied, using in-depth interviews, observation, and documentation. The findings show that the state plays an active role through regulations and village funds, which have supported infrastructure development and improved welfare. However, the introduction of daily wages (HOK) within village programs has shifted the meaning of gotong royong from voluntary communal work to semi-formal participation linked to financial incentives. While gemohing still exists in self-organized community activities outside state programs, its role in official projects has declined. The study concludes that state hegemony produces positive impacts, particularly in infrastructure provision, but also weakens the traditional values of social capital. Therefore, integrating state development policies with local cultural traditions is essential to ensure sustainable village development.